Seed Priming Studies in Cashew: Influence on Softwood Grafting - MEERA MANJUSHA AV; PK RETHEESH (Seed Research, 2026)
A study was conducted at the Kerala Agricultural University, Regional Agricultural Research Station(Northern Zone), Pilicode to study the influence of different seed priming agents on the growth and vigour of therootstock seedlings and its further effect on softwood grafting using the variety Priyanka. The cashew grafts withthe rootstocks grown out of KNO3 3% primed seeds resulted in the highest increase in plant height (10.5%) andthe number of leaves (80.85%) per plant. The optimum time of transplanting cashew grafts is at its age of 5-6months with 5-7 functional leaves and 30-45 cm height. The results show that such quality grafts are obtainedwithin two months when rootstocks are subjected to seed priming withKNO3 3%.Hence the seed priming withKNO3 3% could be recommended as a suitable method for raising quality roots stocks with increased success andvigorous growth through soft wood grafting in cashew.